Towards a Child-Friendly City in East Aceh through Collaborative Governance and Local Challenges - Mukhlis Mukhlis; Muammar Muammar; Fitri Maghfirah (Academia Open, 2025)
General Background: The development of Child-Friendly Cities (CFC) is a strategic initiative to ensure the fulfillment of children's rights in urban governance. Specific Background: Despite national efforts, until 2023, no city or regency in Indonesia has achieved the "Plenary" category of a Child-Friendly City (Kota Layak Anak/KLA). Knowledge Gap: Existing literature lacks a comprehensive understanding of the challenges and model implementations of CFC development in Indonesia. Aims: This study aims to analyze the urgency of KLA development and identify existing models of CFC implementation in Indonesia. Results: Through a qualitative literature review of academic studies, government publications, international organization reports, and media sources, the study finds that collaborative governance involving policymakers, children, and communities is essential for advancing CFC programs. Novelty: The study highlights the need to contextualize child-focused policies to local socio-cultural and developmental needs—an aspect often overlooked in top-down policy approaches. Implications: The findings suggest that sustainable progress toward CFC status requires not only integrated multi-stakeholder collaboration but also adaptive strategies responsive to local child welfare issues, thereby offering a more inclusive and effective policy design framework. Highlights: No Indonesian city has achieved "Plenary" Child-Friendly City status by 2023. Effective CFC development requires collaboration between policymakers, children, and communities. Local context must guide the formulation of child-responsive policies. Keywords: Child Friendly City, Collaborative Governance, Children’s Rights, Urban Policy